2007
DOI: 10.1007/s10750-007-0667-9
|View full text |Cite
|
Sign up to set email alerts
|

Particulate organic carbon in the estuarine turbidity maxima of the Gironde, Loire and Seine estuaries: origin and lability

Abstract: A study of the particulate organic carbon (POC) in the estuarine turbidity maxima (ETMs) of the three major French macrotidal estuaries shows that the average contents are 1.5, 3.3 and 3.1% (expressed in % of dry suspended sediment) in the Gironde, Loire and Seine Estuaries, respectively. There is no seasonal variation of POC contents in the Gironde Estuary, whereas, they often increase in the Loire and the Seine Estuaries in spring and summer. The lability of the estuarine particulate organic matter was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 44 publications
6
87
1
2
Order By: Relevance
“…While current debates on erosion-enhanced sinks of atmospheric CO 2 have focused on reduced decomposition of eroded C under depositional settings (Van Oost et al, 2007;Lal and Pimentel, 2008), recent findings of high biodegradation potentials of POC in large temperate and tropical rivers (Etcheber et al, 2007;del Giorgio and Pace, 2008;Ward et al, 2013) raise an important question as to whether eroded C degrades faster after entering streams and rivers than in source soils. Our measurements of BDOC and optical properties of SS-DOM in the headwater stream suggest that rapid conversion of labile OM between the DOC and POC pools starts to occur even in upstream source areas of mountainous river systems in monsoon Asia, which have been suggested to transport organic C without significant chemical transformations (Galy et al, 2007;Goldsmith et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While current debates on erosion-enhanced sinks of atmospheric CO 2 have focused on reduced decomposition of eroded C under depositional settings (Van Oost et al, 2007;Lal and Pimentel, 2008), recent findings of high biodegradation potentials of POC in large temperate and tropical rivers (Etcheber et al, 2007;del Giorgio and Pace, 2008;Ward et al, 2013) raise an important question as to whether eroded C degrades faster after entering streams and rivers than in source soils. Our measurements of BDOC and optical properties of SS-DOM in the headwater stream suggest that rapid conversion of labile OM between the DOC and POC pools starts to occur even in upstream source areas of mountainous river systems in monsoon Asia, which have been suggested to transport organic C without significant chemical transformations (Galy et al, 2007;Goldsmith et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the bulk of riverine POC at low flow has been considered aged and metabolically not reactive, it has been suggested recently that not only labile components but also recalcitrant compounds such as lignin and other phenolic compounds can be consumed rapidly by microorganisms in large tropical rivers such as the Amazon (Ward et al, 2013). Studies of POC origin and lability in some European estuaries have shown that the bulk of POC in estuaries might be refractory, whereas seasonal changes in the input of organic matter of autochthonous or anthropogenic origin can significantly increase the lability and biodegradability of POC even to a higher degree than observed for DOC (Etcheber et al, 2007;Garnier et al, 2008). It remains unexplored whether POC in headwater streams has comparable lability relative to DOC.…”
Section: Introductionmentioning
confidence: 99%
“…The Gironde Estuary was estimated to contribute 60% of the input of fine sediments to the continental shelf of the Bay of Biscay (Castaing and Allen, 1981). Although this system drains one of the less urbanized/industrialized watersheds in Europe (Abril et al, 2002;Etcheber et al, 2007), it is polluted by heavy metals, preventing oyster and mussel production within the estuary (Latouche, 1988). This chronic metal pollution is due to former mining and smelting activities during the late 19th century in the upper reaches of a tributary (Schäfer et al, 2006;Saari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The vegetation C stocks of delta ecosystems on Hainan Island were three-fold lower than that of the Pearl River Delta [38]. We investigated the fact that the soil of deltas on Hainan Island was sandy, whereas those elsewhere are predominantly loam and clay soils [39], suggesting that the soil texture had a significant influence on vegetation carbon storage. The study of carbon pool in an area of north Nile Delta, Egypt also proved that sand was the most negative factor correlating to C pools [40].…”
Section: Stock Estimates Of Delta Ecosystem Vegetationmentioning
confidence: 99%